AB0639 PREDICTION OF MAJOR VASCULAR COMPLICATIONSIN SYSTEMIC SCLEROSIS (SSC). (June 2019) - Bruni, Cosimo; Rosato, Edoardo; Maestripieri, Vanessa; Gigante, Antonietta; Tesei, Giulia; Chiostri, Marco; Lepri, Gemma; Randone, Silvia Bellando; Guiducci, Serena; Castellani, Sergio; Boddi, Maria; Matucci-Cerinic, Marco
Abstract : Background: in SSc, Digital ulcers (DU), scleroderma renal crisis (SRC) and pulmonary arterial hypertension (PAH) are major vascular complications (MVCs). Among the variables used to follow-up SSc patients, nailfold videocapillaroscopy pattern (NVCp), estimated pulmonary systolic arterial pressure (sPAP), diffusion capacity of carbon oxyde (DLco) and renal resistive index (RRI) on renal vascular Doppler ultrasound have previously shown to be predictive for MVCs development. Moreover, circulating endothelin-1 (ET1) levels have been associated with MVCs. Objectives: to identify clinical, instrumental and laboratory predictors of MVCs development in SSc. Methods: SSc patients fulfilling the 2013 aCR/EULAR criteria were enrolled from two SSc-care units. Data regarding clinical manifestations, instrumental and laboratory evaluation for renal, cardiac and cardiovascular involvement were collected. ET1 serum levels were measured with human ET-1 ELISA kit. Results: 380 patients [aged 57 (46-68) years, 12% males] were enrolled in the study, with 42.4% prevalence of MVCs at baseline. Previously known associations were significantly confirmed between presence of MVCs and NVCp, sPSP, Dlco, RRI. The levels of ET1 were increased in the SSc MVCs without reaching a statistical significance. In the whole population, modified Rodnan skin score (mRSS) [OR 1.081 (95% CI 1.032-1.132), p=0.001], presence of telangectasias [OR 2.246 (95% CI 1.201-4.201), p=0.11] and presence of dyspnoea [OR 2.100 (95%CI 1.029-4.286), p=0.041] were predictive for MVCs at baseline on multivariate regression analysis. During a 3-years follow-up, 21 patients developed a new MVCs and sPAP was the only independent predictor [HR 1.057 (1.016-1.100), p=0.006] at multivariate analysis. When evaluating only MVCs naive patients (n=179), 15 new MVCs developed during the follow-up and joint involvement was the only independent predictors [HR 8.355 (1.741-44.233), p=0.037]. Conclusion: The data show that the most stringent factors predicting MVCs are sPAP and joint involvement in MCVs complicated and naive patients, respectively. These 2 items, together with mRSS and teleangectasias, should always considered in SSc long-term follow up to shape up a tailored therapeutic approach. Acknowledgement: We ackowledge the Italian Society of Rheumatology, who supported Cosimo Bruni in performing this study with a grant. Disclosure of interests: Cosimo Bruni: None declared, Edoardo Rosato: None declared, Vanessa Maestripieri: None declared, antonietta Gigante: None declared, Giulia Tesei: None declared, Marco Chiostri: None declared, Gemma Lepri: None declared, Silvia Bellando Randone: None declared, Serena Guiducci: None declared, Sergio Castellani: None declared, Maria Boddi: None declared, Marco Matucci-Cerinic Grant/research support from: actelion, MSD, Pfizer, BMS, Chemomab, Sanipedia, Speakers bureau: actelion, BMS; MSD, Janssen